5x-3x²+1+(+2x²-3-(5x+2x²-x-4
Soluções para a tarefa
Respondido por
1
-109 e oque apareceu na minha calculadora
alcenimartins:
5x-3x²+1+(+2x²-3-(5x+2x²-x-4
Respondido por
1
5x-3x²+1+(+2x²-3-(5x+2x²-x-4 =
= 5x-3x²+1+ 2x² - 3 - 5x - 2x² + x - 4 =
= - 3x² + x + 2 isto é 3x² - x - 2
= 5x-3x²+1+ 2x² - 3 - 5x - 2x² + x - 4 =
= - 3x² + x + 2 isto é 3x² - x - 2
Perguntas interessantes
Português,
1 ano atrás
Matemática,
1 ano atrás
Matemática,
1 ano atrás
Matemática,
1 ano atrás
Matemática,
1 ano atrás
Filosofia,
1 ano atrás